The Correlation Between Transformational Leadership and Employee Innovation in the Customs Department in the Emirate of Dubai - Salem, Rashed Ismail Bilal; Ismail, Hamidi; Mohammed, Fathey (South Asian Journal of Social Sciences and Humanities, 2023)
Transformational leadership is as an emerging theory in managerial leadership unlike traditional  leadership, where a leader works with his team members by persuading them along with sharing  responsibilities leading to achievement of unexpected results beyond their capabilities.  Management leaders intends to implement transformational leadership style, yet they are unaware  that it is not enough. Therefore, strategic issues like management of knowledge and organizational  learning must be managed through transformational leadership for consulting firms in order to  develop organizational innovation. The research focused on identifying the correlation between  transformational leadership and employee innovation., A quantitative approach relying on a questionnaire was conducted. The study sample consisted of 371 employees who were selected  through quota sampling from Dubai Customs. The results showed that the relative weight of  transformational leadership amounted to 80.34%, with a mean value of 4.02 and a standard  deviation of 0.34, and the relative weight of employee innovation was 67.99%, with an average of  3.40 and a standard deviation of 0.86. The Pearson correlation coefficient between  transformational leadership and employee innovation R=0.269, which means that there is a  correlation between transformational leadership and employee innovation at Dubai Customs in the  United Arab Emirates. In addition, employee innovation was fundamentally affected by the  independent variable (transformational leadership) and in a statistically significant manner.  Furthermore, the findings showed the adjusted coefficient of determination was 0.166, which  means that 16.6% of the change in employee innovation was due to the influence of the  independent variable (transformational leadership). The study may help Dubai Customs in  developing its employees creativity by developing the transformational leadership of its leaders,  and helps it discover strategic elements for this purpose like management of knowledge and  organizational learning.
Keywords: transformational leadership; employee innovation; Dubai Customs; United Arab Emirates